Analysis of predictors of recurrent acute cardiovascular events in patients with acute coronary syndrome - E. I. Usova; L. M. Malishevsky; A. S. Alieva; T. А. Makarova; M. S. Alieva; A. N. Yakovlev; A. O. Conradi (Российский кардиологический журнал)
Aim. To assess the prevalence of traditional risk factors and analyze the predictors of recurrent cardiovascular events in patients with acute coronary syndrome (ACS).Material and methods. A total of 482 patients with ACS were included. The follow-up lasted three years. The composite endpoint (CE) included recurrent unstable angina, nonfatal myocardial infarction, repeated percutaneous coronary intervention (PCI), nonfatal ischemic stroke, hospitalization for decompensated heart failure, and cardiovascular death.Results. A high prevalence of traditional risk factors was revealed (dyslipidemia — 467 (96,9%), hypertension — 464 (96,3%), consumption of junk food — 450 (93,4%), sedentary lifestyle — 416 (86,3%)). During the three-year follow-up period, 90 patients had CE. Compared with patients without CE (n=392), patients with CE were significantly more likely to have a long-term CAD (69 (76,7%) vs 241 (61,5%), p=0,007), ACS accompanied by shortness of breath (50 (55,6%) vs 160 (40,9%), p=0,013); they had previously undergone myocardial revascularization (38 (42,2%) vs 116 (29,6%), p=0,024), often by PCI (36 (40,0%) vs 100 (25,5%), p=0,009), especially in the left main coronary artery (LMCA) (6 (6,7%) vs 3 (0,8%), p=0,002); they were more likely to develop in-hospital acute left ventricular failure (11 (12,2%) vs 18 (4,6%), p=0,012), had a lower hemoglobin level and hematocrit (p<0,05 for all); they more often required intensification of lipid-lowering therapy (86 (100%) vs 334 (85,2%), p=0,002), compliance with which was lower (6 (6,7%) vs 105 (26,8%), p<0,001) than in patients without CE. Previous intervention on the left coronary artery, non-compliance with lipidlowering therapy, hematocrit level 3 months and hemoglobin level 1 year after ACS were predictors of recurrent events. The combination of surgery on left coronary artery and non-compliance with lipid-lowering therapy demonstrated significantly less freedom from CE compared with other patients (77,4% vs 94,6%, p<0,001).Conclusion. A high prevalence of traditional risk factors in the population of patients with ACS was revealed, and potential predictors of recurrent cardiovascular events were identified.